2020
DOI: 10.1002/jcla.23599
|View full text |Cite
|
Sign up to set email alerts
|

miR‐30b‐5p up‐regulation related to the dismal prognosis for patients with renal cell cancer

Abstract: The diagnosis of renal cell carcinoma (RCC) is often made late since there is no early symptom, which thus results in dismal patient prognosis. As a result, new biomarkers are urgently needed and efforts should be made to identify their functions in predicting RCC prognosis. microRNAs (miRNAs) are a class of small noncoding RNAs that are about 20‐22 nucleotides in length, and they have been demonstrated to function as prognostic markers in numerous tumors. This study aimed to assess the role of miR‐30b‐5p in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, Wu et al 40 found that miR-30b-5p promoted the proliferation, migration and invasion of breast cancer cells. Moreover, the diagnostic and prognostic value of miR-30b-5p in peripheral blood and tumor tissues for renal cell carcinoma and breast cancer had been explored [41][42][43] . Our study demonstrated that hypoxic pancreatic cancer cells promoted angiogenesis through transferring exosomal miR-30b-5p to endothelial cells to regulate directly the expression of GJA1.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wu et al 40 found that miR-30b-5p promoted the proliferation, migration and invasion of breast cancer cells. Moreover, the diagnostic and prognostic value of miR-30b-5p in peripheral blood and tumor tissues for renal cell carcinoma and breast cancer had been explored [41][42][43] . Our study demonstrated that hypoxic pancreatic cancer cells promoted angiogenesis through transferring exosomal miR-30b-5p to endothelial cells to regulate directly the expression of GJA1.…”
Section: Discussionmentioning
confidence: 99%